2020
DOI: 10.1017/s0714980820000148
|View full text |Cite
|
Sign up to set email alerts
|

Age-Friendly Communities and Cultural Pluralism: Examining Saskatoon’s Chinese-Canadian Social Enclave

Abstract: This article uses findings from qualitative interviews to examine the experiences of members of Saskatoon’s Chinese-Canadian older-adult community in terms of their realities of aging and access to important geriatric resources. Promoting an understanding of both group experience and a broader conceptualization of age-friendly development, we argue that the notion and implications of a spatial ethnic enclave are replaced in the Saskatoon context by a social enclave. This network of social support is evident in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Increasing the capabilities of health and care services to provide culturally specific care is necessary as language barriers, lack of bilingual staff, and staff spending less time with people who did not speak the same language were barriers for culturally and linguistically diverse people living with dementia (City of North Vancouver, 2020; Darlington et al, 2021; Department of Local Government, Sport and Cultural Industries, 2017; Herman et al, 2021; Telfar 2014). Traditional kinship and caregiving roles within families also impacted engagement with support services (Dean et al, 2015; Department of Local; Government, Sport and Cultural Industries, 2017; Nelson & Rosenberg, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the capabilities of health and care services to provide culturally specific care is necessary as language barriers, lack of bilingual staff, and staff spending less time with people who did not speak the same language were barriers for culturally and linguistically diverse people living with dementia (City of North Vancouver, 2020; Darlington et al, 2021; Department of Local Government, Sport and Cultural Industries, 2017; Herman et al, 2021; Telfar 2014). Traditional kinship and caregiving roles within families also impacted engagement with support services (Dean et al, 2015; Department of Local; Government, Sport and Cultural Industries, 2017; Nelson & Rosenberg, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The new papers can still reflect the theoretical trend found in the analysis of this study. It validated that scholars still use the six groups of theories to study age-friendly community: (1) ecological theory [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ], (2) the production of space [ 156 , 157 , 158 , 159 , 160 , 161 ], (3) social-related theories [ 98 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ], (4) place-related theories [ 170 , 171 , 172 , 173 , 174 , 175 , 176 ], (5) governing-related theory [ 177 , 178 , 179 , 180 , 181 ], and (6) individual-centred theories [ 182 , 183 , 184 , 185 , 186 , 187 , 188 ]. In addition, more researchers find the importance of studying the social dynamic and individual experience in age-friendly community development.…”
Section: Discussionmentioning
confidence: 99%
“…This study forms a part of a larger project entitled "Age-Friendly For Whom?" that explored diverse perspectives on age-friendly cities from immigrant, racialized, Indigenous and LGBTQ2S+ communities (Herman et al, 2020). 2 The results of the present study are not intended to be authoritative, but rather to spark discussion on the ways in which the needs of older Indigenous people may be incorporated into age-friendly city planning.…”
Section: Canadian Journal On Aging / La Revue Canadienne Du Vieillissementmentioning
confidence: 99%
“…As examples of some of the findings, Rosenberg, Walker, and Wilson (2016) showed that many of the basic services required for an age-friendly community (e.g., subsidized housing for lowincome older people) had waiting times in excess of 12 months, or rules and regulations limiting the value of the services (e.g., the use of access vans). In a sub-study focusing on one ethnic group, Herman, Walker, and Rosenberg (2020) report on the challenges faced by older Chinese Canadians living in Saskatoon.…”
Section: Canadian Journal On Aging / La Revue Canadienne Du Vieillissementmentioning
confidence: 99%